Aortic Valve Disease and Vascular Mechanics: Two‐Dimensional Speckle Tracking Echocardiographic Analysis. Issue 8 (16th April 2016) - Leite, Luís; Teixeira, Rogério; Oliveira‐Santos, Manuel; Barbosa, António; Martins, Rui; Castro, Graça; Gonçalves, Lino; Pego, Mariano
Abstract : Purpose: Degenerative aortic valve disease (AVD) is a complex disorder that goes beyond valve itself, also undermining aortic wall. We aimed to assess the ascending aortic mechanics with two‐dimensional speckle tracking echocardiography (2DSTE) in patients with aortic regurgitation (AR) and hypothesized a relationship with degree of AR. Aortic mechanics were then compared with those of similarly studied healthy controls and patients with aortic stenosis (AS); finally, we aimed to assess the prognostic significance of vascular mechanics in AVD. Methods: Overall, 73 patients with moderate‐to‐severe AR and 22 healthy subjects were enrolled, alongside a previously examined cohort (N = 45) with moderate‐to‐severe AS. Global circumferential ascending aortic strain (CAAS) and strain rate (CAASR) served as indices of aortic deformation; corrected CAAS was calculated as CAAS/pulse pressure (PP). Median clinical follow‐up was 438 days. Results: In patients with severe (vs. moderate) AR, CAASR (1.53 ± 0.29/sec vs. 1.90 ± 0.62/sec, P < 0.05) and corrected CAAS (0.14 ± 0.06%/mmHg vs. 0.19 ± 0.08%/mmHg, P < 0.05) were significantly lower, whereas CAAS did not differ significantly. Measurers of aortic mechanics (CAAS, corrected CAAS, CAASR) differed significantly (all P < 0.01) in patients with AS and AR and in healthy subjects, with lower values seen in patients with AS. In follow‐up, survival rate of AVD patients with baseline CAASR >0.88/sec was significantly higher (log rank, 97.4% vs. 73.0%; P = 0.03). Conclusions: Quantitative measures of aortic mechanics were lower for AS patients, suggesting a more significant derangement of aortic elastic properties. In the context of AVD, vascular mechanics assessment proved useful in gauging clinical prognosis.